Technology evolution from self-powered sensors to AIoT enabled smart homes. (January 2021) - Dong, Bowei; Shi, Qiongfeng; Yang, Yanqin; Wen, Feng; Zhang, Zixuan; Lee, Chengkuo
Abstract: The need of self-powered sensors and self-sustainable micro-/nano-systems is increasing for smart home applications. With the aid of the fifth-generation (5G) wireless communication and the artificial intelligence (AI) technology, numerous sensors can form an artificial intelligence of things (AIoT) system with a cloud computing server to collect, store, process, analyze data, and control the system. In this review, we briefly introduce the major sensor transducing mechanisms and the corresponding representative sensors. Then we emphasize the discussion of triboelectric sensors and their use as various types of human machine interfaces (HMIs). Regarding integrated self-sustainable systems with energy storage function for more general application scenarios, we present the recent advances of integration of triboelectric nanogenerator with supercapacitors, lithium-ion batteries, and solar cells. The development of materials and configurations with novel functionalities to improve the system performance are discussed. We present the state-of-the-art works based on the synergy between wearable sensors and AI technology, highlighting the system-level function of analyzing abundant sensory data, recognizing events, and making decisions accordingly. We wrap up the review by providing our perspectives of future development of self-powered sensors and self-sustainable micro-/nano-systems towards improved wearability, multifunctionality, better self-sustainability via multi-domain energy harvesting and storage technology integration, and higher-level intelligence for complex scenarios. Graphical Abstract: ga1 Highlights: Evolution from self-powered sensors to self-sustainable micro-/nano-systems for 5G smart homes in the AIoT era was reviewed. Recent advances of self-powered physical sensors, chemical sensors, and human-machine interfaces were presented. System integration of TENGs and energy storages towards self-sustainable micro-/nano-systems was summarized. Fusion of AIoT and self-sustainable micro-/nano-systems was highlighted.